HUBUNGAN JUMLAH LIMFOSIT TOTAL DENGAN STATUS NUTRISI PADA PASIEN DIABETES MELITUS TIPE 2 RAWAT INAP DI RUMAH SAKIT UMUM PUSAT SANGLAH DENPASAR TAHUN 2014 - ¬Ni Putu Ade Tiwi Tyastarini Tyastarini; Made Ratna Saraswati (Universitas Udayana, 2017)
WHO has predicted that deaths from diabetes will be doubled from 2005 to 2030. According to the WHO, patients with DM in Indonesia will increase from 8.4 million in 2000 to 21.3 million in 2030. According to some data in 2011 showed total diabetes patients in Sanglah Hospital, Bali as many as 974 people. This study uses a cross-sectional study to determine the relationship between Total Lymphocyte Count (TLC) with nutritional status in patients with type 2 diabetes mellitus hospitalizations in Sanglah Hospital. When the study is over 12 months in 2014 which will be held in the Inpatient internal medicine faculty medicine of udayana university / Sanglah Hospital. In this study, 98 samples that meet the inclusion and exclusion criteria. The sample consisted of 55 male (56.1%) and 43 women (43.9%). The average age of the sample was 56 years with a standard deviation of 9.9. The average HbA1C of patients was 9.23% with 16 data that has not known the results of the tests. 11 patients (11.2%) had good glycemic control (HbA1C <6.5%) and 71 patients (72.4%) had poor glycemic control (HbA1c ? 6.5%). Of all the samples studied, a total of 91 patients (92.9%) who experienced various complications whereas only 7 patients (7.1%) is DM patients without complications. From the Post-Hoc test was obtained was not significant when seen differences in the number of lymphocytes among the five complications with the group that there are no complications. When analyzed further to determine the mean difference by looking at the results of the analysis of Post Hoc to three groups of nutritional status, the data showed that the group's nutritional status well with the medium, p <0.001, CI 95% not covered numbers 0 and between groups of nutrients well with bad p <0.001, CI 95% not covered zeros. Thus, the difference TLC significantly different between both groups of nutrients with moderate or good with the bad. Keywords: Diabetes mellitus (DM), Total Lymphocyte Count (TLC), nutrients.